Student Stress and Anxiety in an Educational Perspective - Zihori Maulida; M Zainul Hafizi (Chatra: Jurnal Pendidikan dan Pengajaran, 2026)
This study explores the experiences of stress and anxiety among students at the Institut Pendidikan Nusantara Global (IPNG), focusing on their causes, manifestations, and coping strategies. Employing a descriptive qualitative approach, data were collected through in-depth interviews, observation, and documentation, and analyzed thematically to capture holistic patterns and themes of student experiences. Findings indicate that students experience multidimensional stress encompassing cognitive, emotional, and physical aspects, including fatigue, sleep disturbances, and feelings of being overwhelmed. To manage stress, students employ various coping strategies such as social support, time management, and relaxation activities. The study underscores the importance of a holistic approach combining the enhancement of students’ internal capacities with the management of a supportive and responsive academic environment. Practical implications include the development of counseling programs, stress management workshops, and adaptive academic policies. The study’s limitations concern generalizability, as data were collected solely from IPNG students and are context-specific. Penelitian ini bertujuan mengeksplorasi pengalaman stres dan kecemasan mahasiswa di Institut Pendidikan Nusantara Global (IPNG), dengan fokus pada faktor penyebab, manifestasi, dan strategi coping yang diterapkan. Penelitian menggunakan pendekatan kualitatif deskriptif dengan pengumpulan data melalui wawancara mendalam, observasi, dan dokumentasi, serta analisis tematik untuk mengidentifikasi pola dan tema pengalaman mahasiswa secara holistik. Hasil menunjukkan bahwa mahasiswa mengalami stres multidimensional yang melibatkan aspek kognitif, emosional, dan fisik, termasuk kelelahan, gangguan tidur, dan perasaan kewalahan. Untuk mengatasi hal ini, mahasiswa mengembangkan berbagai strategi coping, seperti dukungan sosial, manajemen waktu, dan aktivitas relaksasi. Temuan menekankan pentingnya pendekatan holistik yang memadukan penguatan kapasitas internal mahasiswa dengan pengelolaan lingkungan akademik yang suportif dan responsif. Implikasi praktis meliputi pengembangan program konseling, workshop manajemen stres, dan kebijakan akademik yang adaptif. Keterbatasan penelitian terkait pada generalisasi, karena data hanya berasal dari mahasiswa IPNG dan sifat kualitatif yang kontekstual.